The use of communicative strategies to facilitate the learning english languaje in preeschool at Cambrigde Bilingual School - Miranda Vigil, Joelys Adalith (UDELAS, 2015)
This report consist of three chapters in which all the information collected is set during this period of investigation at Cambridge Bilingual School.